EFFICACY AND SAFETY OF VEDOLIZUMAB AND TUMOR NECROSIS FACTOR INHIBITORS IN THE TREATMENT OF STEROID-REFRACTORY MICROSCOPIC COLITIS: A SYSTEMATIC REVIEW AND META-ANALYSIS. (26th January 2023) - Chehade, Nabil El Hage; Shah, Sagar; Pardi, Darrell; Farraye, Francis; Al Hashash, Jana
Abstract: BACKGROUND: Tumor necrosis factor (TNF-α) inhibitors and the α4β7 integrin antagonist, vedolizumab have been investigated as a treatment option for patients with steroid-refractory microscopic colitis (MC) with controversial findings. AIMS: To perform a systematic review and meta-analysis to evaluate the benefit of vedolizumab and TNF-α inhibitors in patients with steroid-refractory MC. METHODS: Retrospective cohort studies and case series involving adult patients with steroid-refractory MC who either received vedolizumab, adalimumab, or infliximab were eligible for inclusion. Outcomes of interest included the rate of clinical remission at induction, clinical response, maintenance of remission, histologic remission, and overall medication related adverse effects. Pooled proportional meta-analyses were used to calculate the overall rates of the primary and secondary endpoints. Heterogeneity was assessed using the I 2 statistic. Publication bias was assessed via visual inspection of the funnel plots and using Egger's regression. All statistical analysis was performed in R using the metafor and meta packages. RESULTS: A total of 14 retrospective case series/studies involving 164 patients were included. Pooled analysis showed a clinical remission rate of 63.5% (95% CI [0.483; 0.776], I 2 =43% P=0.08), 57.8% (95% CI [0.3895; 0.7571], I 2 =0%, P=0.7541), and 39.3% (95% CI [0.0814; 0.7492, I 2 =66%, P=0.02) for vedolizumab, infliximab, and adalimumab, respectively. The maintenance of remission rate was 60.5% (95% CI [0.2772; 0.8953], I 2 =67%, P=0.03), 45.3% (95% CI [0.1479; 0.7747], I 2 =0%, P=0.36) and 32.5% (95% CI [0.000; 0.8508], I 2 =53%, P=0.14) in patients who received vedolizumab, infliximab, and adalimumab, respectively. Rate of biologic-related adverse events warranting discontinuation of therapy was 12.2%, 32.9%, and 23.0% for the vedolizumab, infliximab, and adalimumab groups, respectively. CONCLUSION: Vedolizumab and anti-TNF-α agents demonstrated a clinical benefit in the treatment of steroid-refractory MC and with a tolerable safety profile. Given the nature of included studies, superiority of either therapy could not be elucidated. Future randomized controlled trials are needed to standardize study protocols, compare vedolizumab with TNF-α inhibitors, and further examine data on patients' quality of life. Forest plot showing the pooled clinical remission rate at induction in patients with steroid-refractory microscopic colitis receiving (A) vedolizumab or TNF inhibitors (B) Data summary of the meta-analyses of the studies investigating secondary endpoints in patients with refractory MC receiving either (A) vedolizumab or (B) TNF inhibitors ABBREVIATIONS: MR, maintenance remission; CR, clinical response; HR, histologic remission; OAE, overall adverse effects.